HR Practices, Employment Engagement, Job Crafting, Organizational Citizenship Behavior Affect Task Performance (Bekasi City Banking Company) - Tigor Maruhum Hutapea; Rhian Indradewa; Tantri Yanuar R Syah; Diana Fajarwati (Journal of Multidisciplinary Academic, 2021)
Employee performance is determined by several factors, including employee development practices, work engagement, organizational citizenship behaviour, task performance, and job creator. Here, the implementation of several, factors has become important points during improving job performance to achieve Company's goals. However, the implementation factors are interrelated with job performance improvement. In this study, we use a quantitative approach with a survey method to obtain leadership effects on organizational learning and organizational innovation in shaping of organizational performance. Here we were distributed questionnaires to 300 employees of banking companies in Bekasi City, then the data were analysed using the PLS Structural Equation Modelling (SEM) method. The result show in the fact that these factors can really affect the performance of employees in companies in the banking sector, where comparisons will be made. how these factors influence in improving employee performance.